Awareness and Sources of Climate Change Information among Secondary School Students in Nairobi County, Kenya - Gichuki, Mutahi William (2014)
The study investigated the awareness and sources of climate change information among the secondary school students in Nairobi County. The objectives of the study were to find out whether students and teachers are aware of climate change and their sources of information on climate change. It also investigated the extent to which climate change information has been covered in the integrated environmental education. The study applied the descriptive survey design. The target population consisted of secondary schools students and teachers in Nairobi County and curriculum development officer from KIE. The sample consisted of 792 students, 198 teachers from 18 secondary schools and I officer from Kenya institute of education. The sample was drawn using stratified, purposive and simple random sampling techniques .The reliability of instruments was ensured by conducting three pilot surveys. The data was collected through the use of questionnaires for the students and the teachers and an interview schedule for the Kenya institute of education officer. Data was analyzed using the statistical package for social sciences (SPSS). Chi- square Test was used to determine relationship between variables (p<0.05). The finding revealed a low level of climate change awareness among students of secondary schools in the study area. The student's knowledge of causes and effect of climate change were inadequate. There was significant association between student's knowledge on climate change and willingness to be involved in climate change mitigation activities (p=0.000). Although majority of the teachers were aware of global climate change their knowledge on climate change is inadequate to teach it. There was significant association between students and teachers sources of information on climate change and gender (p=0.001I).The media was the main source of climate change information for both the students and the teachers. Climate change topics were not adequately covered in integrated environmental education. The study recommends that climate change awareness activities be included in the existing Environmental clubs in schools so as to mobilize the students on the importance of bracing up to the challenges of climate change and also creating climate change awareness. The schools should be equipped with relevant learning materials to ensure students have an access to correct information on climate change. The teachers should be in- serviced to able to effectively teach climate change topics. The integrated environmental education should be reviewed to include more climate change topics. Further research on students awareness and sources of climate change information in other counties, how the media influence students perception of global climate change, teachers awareness of climate change issues in other county and efforts made by different institution in creating climate change awareness in Kenya.
openalex:W1957781434 mag:1957781434 KerkoCite.ItemAlsoKnownAs: 5072953:W7Z3QTPV
Keywords: C:Kenya; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change information; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes